New Geometrical Aspects Regarding ZPA Worms. (2015) - Pozdirca, Alexandru
Abstract: The article presents new geometrical aspects regarding the ZPA worms - introduced by the author (a worm generated on NC lathe with standard cylindrical milling tools). First, the article reminds the definition of the ZPA worm and then presents details regarding the root fillet of worm's flank. In this regard is determined the contact line of a torus end mill tools and the helicoidally generated surface. This process is assisted by a CAD software, developed by the author. Controlling of the root fillet area is important to protect the edge of the flank finishing milling tool. The advantages of the ZPA worm type are: (i) the use of standard tools with reduced costs and also short processing time; (ii) the possibilities to cover other standard worms, using the standard cylindrical milling tools and non-specialized NC machining tools.